Angiogenesis factors and placental hormones in the first trimester of pregnancy of women with arterial hypertension of stage 1 and 2 with further fetal growth retardation - Deinichenko, Olena; Krut, Yuriy (Journal of Education, Health and Sport, 2019)
The disbalance of pro-angiogenic and anti-angiogenic factors, hormonal balance shift in fetal growth retardation (FGR) among high-risk pregnant women plays a significant role in the pathogenesis of this pathological condition and may serve as a prognostic criterion in early pregnancy. Materials and methods. We conducted a prospective study of 88 pregnant women at 12-13 weeks of pregnancy. The pro-angiogenic placental growth factor (PIGF) and anti-angiogenic – placental soluble fms-like tyrosine kinase (sFlt-1) and their ratio (sFlt-1/PIGF coefficient) were determined. Estradiol (E), progesterone (PG), and chorionic gonadotropin (CG) were determined among the placental hormones. Results. PIGF was statistically significantly reduced in pregnant women with FGR (6,7 pg/ml) comparing to the results of group 2 (18,7 pg/ml; p˂0,05) and it was reduced comparing to group 3 (15,5 pg/ml; 0,05˂ p˂0,1). The levels of sFlt-1, by contrast, were highest among the women in group 1: (1972,3 pg/ml; p˂0,05) compared to the control group (1384,4 pg/ml) and compared to 3 group (1595,3 pg/ml; 0,05˂p˂0,1). sFlt-1/PIGF was significantly higher for patients of group 1 (596,5 units) compared to group 2 (252,2 units), р˂0,05. Conclusion. In pregnant women with hypertension of 1 and 2 degrees, which in the first trimester of pregnancy (12-13 weeks of gestation) there was the decrease in levels of PIGF, increase in sFlt-1 levels and increase in the sFlt-1/PIGF ratio, the fetal growth retardation develops in future in comparison to women without hypertension. The levels of PIGF are significantly lower and the coefficient values are higher than those ones of pregnant women with hypertension of 1st degree. The levels of placental hormones of this pathology are not statistically significantly different from the data of the control group.